Preparation method and application of novel anode IrO2atWC / WO3 composite catalyst suitable for proton exchange membrane water electrolyser technology
Through the preparation of porous IrO2@WC/WO3 composite catalyst, the problem of slow kinetics of PEMWE anode oxygen precipitation reaction is solved, the amount of iridium is used and the catalytic activity is improved, and the efficient oxygen precipitation reaction is achieved, which promotes the performance of PEMWE technology. Improve and reduce costs.
Patent Information
- Application Number
- CN202411652824.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-27
AI Technical Summary
In the existing proton exchange membrane water electrolytic cell (PEMWE) technology, the kinetics of the anode's oxygen precipitation reaction are slow, resulting in high catalyst costs and relying on precious metal platinum group catalysts, which limits the widespread promotion of the technology.
Using porous IrO2@WC/WO3 composite catalyst, the mixture of sodium tungstate and sodium nitrate was heated and stirred in isopropanol and ethanol to form a WO3 nanocarrier, which was then ball milled with a carbon source and sintered at high temperature, and finally added to the hydrothermal reaction. Ammonium persulfate and ammonium fluoride synthesize IrO2@WC/WO3 composite catalyst, significantly reducing the amount of iridium and improving catalytic activity.
It significantly improves the catalytic activity and durability of the catalyst, reduces the amount of iridium, has better catalytic performance than commercial IrO2 catalysts, has increased ECSA by 1.8 times, and has an oxygen precipitation potential of 270-300 mV, and has better catalytic activity than commercial oxidation at the same current density. Iridium catalyst.
Smart Images

Figure CN119194494A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and specifically relates to a preparation method and application of a novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology. Background Art
[0002] The global climate is adversely affected by fossil fuels every year. Hydrogen, a clean energy source, brings a better future to the world. In addition, the power density of hydrogen is three times that of gasoline and diesel. Proton exchange membrane water electrolyzer (PEMWE) hydrogen synthesis is a green production process with no pollution and zero carbon emissions.
[0003] my country's vast western region is rich in a large amount of intermittent sustainable green energy such as solar energy and wind energy. Therefore, by using the "abandoned electricity" such as abandoned light, abandoned wind, and abandoned water in the western region to produce hydrogen through water electrolysis, it is easy to obtain green hydrogen with high power density. Then the prepared hydrogen is used as fuel for proton exchange membrane fuel cells (PEMFC), which can make more efficient use of these green hydrogen. However, these systems have some shortcomings that need to be overcome. As we all know, cost issues are the focus of attention in energy conversion systems. Using high-purity hydrogen as fuel for fuel cells is one of the shortcomings of this system. Of course, the relatively expensive platinum group precious metals (Pt, etc.) used in fuel cells is also one of the shortcomings of this system. In response to this problem, many researchers are working hard to reduce the cost of platinum group precious metal catalysts. In order to cooperate with the further promotion of fuel cell systems, how to obtain high-purity hydrogen efficiently and cheaply through PEMWE is also one of the important issues that need to be solved.
[0004] In the PEMWE technology route, the kinetic process of the oxygen evolution reaction (OER) at the anode is many times slower than the hydrogen evolution (HER) process at the cathode. Therefore, the development of efficient and inexpensive OER catalysts plays an important role in improving the performance of PEMWE and reducing its cost. Usually, the anode of PEMWE requires IrO2 catalyst, which has good catalytic activity and excellent durability. However, the extreme scarcity of iridium resources has caused the high cost of the PEMWE technology route, which is not conducive to the widespread promotion of this technology. Therefore, we propose to replace the iridium precious metal with a transition metal compound to obtain a composite catalyst confined by a transition metal framework. Summary of the invention
[0005] The purpose of the present invention is to overcome some technical defects of the existing PEMWE catalysts, and proposes a method for preparing a highly efficient porous IrO2@WC / WO3 composite catalyst of IrO2 confined by a transition metal WC / WO3 compound. Compared with the existing IrO2 catalyst, the composite catalyst can significantly reduce the amount of iridium used, wherein WC has a charge density distribution similar to that of Pt, Pd, Ir, etc., and therefore can significantly replace the precious metal iridium, while also improving its catalytic activity and durability.
[0006] A method for preparing a novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology comprises the following steps: (1) Sodium tungstate and sodium nitrate are added to a mixed solution of isopropanol and ethanol, and then stirred under heating conditions until completely dry, ball milled, and sintered at high temperature to obtain a WO3 nanocarrier through the action of molten salt, cooled to room temperature, centrifuged and washed, and dried to obtain the final WO3 nanocarrier; (2) The final WO3 nano-carrier obtained in step (1) is mixed with the carbon source by ball milling, transferred to a tube furnace, sintered at high temperature, cooled to room temperature, centrifuged and washed, and dried to obtain a WC / WO3 composite carrier; (3) The WC / WO3 composite support, ammonium persulfate, ammonium fluoride and iridium salt obtained in step (2) are added to a hydrothermal reactor, and a methanol solution is added, ultrasonically dispersed, heated to 180 degrees and kept warm for 4-8 hours, cooled to room temperature, centrifuged and washed, and dried to obtain an IrO2@WC / WO3 composite catalyst.
[0007] Preferably, in step (1), the molar ratio of sodium tungstate to sodium nitrate is 1:(10-40), and the volume ratio of isopropanol to ethanol is 1:1.
[0008] Preferably, the stirring under heating conditions until completely dry in step (1) specifically comprises: heating to 60-80° C., stirring for 1-3 h, and then adjusting the temperature to 100° C. and stirring until completely dry; the ball milling speed is 100 rpm / min, and the time is 30 min.
[0009] Preferably, the high temperature sintering conditions in step (1) are: heating to 350-750°C at a heating rate of 2-5°C / min and calcining for 1-3h.
[0010] Preferably, the carbon source in step (2) is urea, melamine, glucose or chitosan; wherein the high temperature sintering in step (2) is as follows: introducing a H2 mixed gas with a flow rate of 20-100 sccm and a 10% Ar / H2 ratio, heating to 1000-1200°C at a heating rate of 2°C / min, and calcining for 1-3h.
[0011] Preferably, the mass ratio of the WO3 nanocarrier to the carbon source in step (2) is 1:10.
[0012] Preferably, the centrifugal washing conditions in steps (2) and (3) are: centrifugation at 7000-10000 rpm / min for 3-5 times.
[0013] Preferably, the drying in steps (1), (2) and (3) is vacuum drying at a temperature of 50-80° C. for 5-10 hours.
[0014] Preferably, in step (3), the added mass ratio of the WC / WO3 composite carrier to the iridium content in the iridium salt is (1:0.2); the molar ratios of ammonium persulfate, ammonium fluoride and iridium in the iridium salt are (1:1:0.5) respectively; and the iridium salt is iridium trichloride, chloroiridic acid, iridium acetate, ammonium chloroiridate or potassium hexachloroiridate.
[0015] The catalyst is used in the electrolysis of oxygen in acidic water.
[0016] Advantages of the present invention: (1) The present invention obtains a porous IrO2@WC / WO3 composite catalyst having IrO2 confined in a transition metal WC / WO3 compound by molten salt sintering and hydrothermal synthesis. Since the catalyst has a large number of pore structures, the IrO2 active sites on the surface and inside can fully contact with the reactants, while promoting the rapid separation of the product O2 and accelerating the mass transfer process of the catalyst. (2) The composite catalyst prepared by the present invention has good catalytic performance and high specific surface area. Compared with the existing commercial IrO2 catalyst, the ECSA is increased by 1.8 times, and the oxygen evolution potential is 270-300 mV when the current density reaches 10 mAcm-2. The catalytic activity is better than that of the commercial iridium oxide catalyst at the same current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 SEM spectrum of the catalyst prepared in Example 2.
[0018] Figure 2 N2 isothermal absorption / desorption curve of the catalyst prepared in Example 2.
[0019] Figure 3 Pore size data distribution diagram of the catalyst prepared in Example 2.
[0020] Figure 4 Polarization current curves of the catalysts prepared in Examples 1-3 and commercial IrO2 catalysts.
[0021] Figure 5Double layer capacitance values of the catalyst prepared in Example 2 and the commercial IrO2 catalyst.
[0022] Figure 6 Electrochemical impedance spectra of the catalysts prepared in Examples 1-3 and commercial IrO2 catalysts. DETAILED DESCRIPTION
[0023] Example 1 A method for preparing a novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology comprises the following steps: (1) 5.8 g (20 mmol) of sodium tungstate and 34 g (400 mmol) of sodium nitrate were added to a mixed solution of 50 ml of isopropanol and 50 ml of ethanol, and then heated to 80 °C and stirred for 3 h. Then the temperature was adjusted to 100 °C and stirred until completely dry. The mixture was ball milled at a speed of 100 rpm / min for 30 min. Then the mixture was transferred to a furnace and heated to 500 °C at a speed of 2 °C / min. Then the mixture was sintered at 500 °C for 2 h. After cooling to room temperature, the mixture was centrifuged and washed for 5 times at a speed of 8000 rpm / min. The mixture was vacuum dried at 60 °C for 6 h to obtain the final WO3 nanocarrier. (2) Weigh 1 g of the final WO3 nanocarrier obtained in step (1) and 10 g of urea, mix them evenly by ball milling at 100 rpm / min for 30 min, transfer them to a tube furnace, introduce a H2 mixture with a 10% Ar / H2 ratio at a flow rate of 100 sccm, heat to 1000°C at a heating rate of 2°C / min, and maintain for 3 h. After cooling to room temperature, centrifuge and wash them at 8000 rpm / min for 5 times, maintain vacuum drying at 60°C for 6 h, and obtain a WC / WO3 composite carrier; (3) Weigh 1 g of WC / WO3 composite support, 0.57 g (1.4 mmol) H2IrCl6·6H2O, 0.475 g (2.08 mmol) of (NH4)S2O8 and 0.074 g (2.08 mmol) of NH4F into a 100 ml hydrothermal reactor, and add 60 mL of methanol solution. After ultrasonic dispersion for 30 min, heat to 180 °C and keep warm for 8 h. After cooling to room temperature, centrifuge and wash at 8000 rpm / min for 5 times, maintain vacuum drying at 60 °C for 6 h, and finally obtain IrO2@WC / WO3 composite catalyst.
[0024] Example 2 In step (2), the calcination temperature is 1100°C, the iridium salt is: 0.455 g (1.03 mol) of (NH4)3IrCl6, and the rest is the same as in Example 1.
[0025] Example 3 In step (2), the calcination temperature is 1200° C., and the rest is the same as in Example 1.
[0026] Example 4 In step (2), the carbon source was changed to melamine, the iridium salt was 0.502 g (1.04 mmol) of K2IrCl6, and the rest was the same as in Example 1.
[0027] Example 5 A method for preparing a novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology comprises the following steps: (1) Add 5.8 g (20 mmol) of sodium tungstate and 68 g (800 mmol) of sodium nitrate to a mixed solution of 100 ml of isopropanol and 100 ml of ethanol, and then heat to 75℃ Stirring 3 h, then adjust the temperature to 100 ° C and stir until completely dry, ball mill at a speed of 100 rpm / min for 30 min, then transfer to a Ma Fei furnace and heat to 750 ° C at 5 ° C / min, then keep 750 ° C sintering for 3 h, cool to room temperature, centrifuge and wash 5 times at a speed of 10000 rpm / min, keep 80 ° C vacuum drying for 5 h, and obtain the final WO3 nano-carrier; (2) Weigh 1 g of the final WO3 nanocarrier obtained in step (1) and 10 g of glucose, mix them evenly by ball milling at 100 rpm / min for 30 min, transfer them to a tube furnace, introduce a H2 mixture with a 10% Ar / H2 ratio at a flow rate of 100 sccm, heat to 1000°C at a heating rate of 2°C / min, calcine for 3 h, cool to room temperature, centrifuge and wash for 5 times at a speed of 10000 rpm / min, maintain vacuum drying at 80°C for 5 h, and obtain a WC / WO3 composite carrier; (3) Weigh 1 g of WC / WO3 composite support, 0.4 g (0.377 mmol) C 12 H 18 Ir3O 13 ·C2H3O2·3(H2O), 0.475g (2.08 mmol) of (NH4)S2O8 and 0.074g (2.08 mmol) of NH4F were added into a 100ml hydrothermal reactor, and 60mL of methanol solution was added. After ultrasonic dispersion for 30min, the mixture was heated to 180℃ and kept for 8h. After cooling to room temperature, the mixture was centrifuged and washed for 5 times at 10000rpm / min, and vacuum dried at 80℃ for 5h to obtain the IrO2@WC / WO3 composite catalyst.
[0028] Example 6 (1) Add 5.8 g (20 mmol) of sodium tungstate and 17 g (200 mmol) of sodium nitrate to a mixed solution of 25 ml of isopropanol and 25 ml of ethanol, then heat to 60 °C and stir for 1 h, then adjust the temperature to 100 °C and stir until completely dry, ball mill at 100 rpm / min for 30 min, then transfer to a Mabo furnace and heat to 350 °C at 2 °C / min, then maintain 350 °C for 1 h, cool to room temperature, centrifuge and wash 3 times at 7000 rpm / min, maintain 50 °C for vacuum drying for 10 h, and obtain the final WO3 nanocarrier; (2) Weigh 1 g of the final WO3 nanocarrier obtained in step (1) and 10 g of chitosan, mix them evenly with the mixture by ball milling at 100 rpm / min for 30 min, transfer them to a tube furnace, introduce a mixture of Ar / H2 with a flow rate of 100 sccm of H2 and 10% of H2, heat them to 1000°C at a heating rate of 2°C / min, calcine them for 3 h, cool them to room temperature, centrifuge and wash them 3 times at 7000 rpm / min, maintain vacuum drying at 50°C for 10 h, and obtain a WC / WO3 composite carrier; (3) Weigh 1 g of WC / WO3 composite support, 0.31 g (1.04 mmol) IrCl3, 0.475 g (2.08 mmol) (NH4)S2O8 and 0.074 g (2.08 mmol) NH4F into a 100 ml hydrothermal reactor, and add 60 mL of methanol solution. After ultrasonic dispersion for 30 min, heat to 180 °C and keep warm for 8 h. After cooling to room temperature, centrifuge and wash for 3 times at 7000 rpm / min, maintain vacuum drying at 50 °C for 10 h, and finally obtain IrO2@WC / WO3 composite catalyst.
[0029] Performance Testing 1.SEM inspection The IrO2@WC / WO3 composite catalyst obtained in Example 2 was subjected to SEM examination. Figure 1 It can be seen that the catalyst has a rich pore structure.
[0030] 2. N2 isothermal adsorption / desorption detection Figure 2 The N2 isothermal adsorption / desorption curve of the IrO2@WC / WO3 composite catalyst prepared in Example 2. It can be seen that the adsorption and desorption curve is a typical type IV characteristic isotherm. It has the characteristics of convexity in the low-pressure area, capillary condensation in the high-pressure area, non-overlapping adsorption and desorption processes, and adsorption hysteresis loops, indicating that the composite material has a large number of mesopores. The BET specific surface area of the catalyst is 251.32 m 2 / g.
[0031] 3. Pore size distribution detection The pore size distribution data of the IrO2@WC / WO3 composite catalyst prepared in Example 2 was obtained during the N2 isothermal adsorption / desorption test. The pore size data distribution diagram is shown in Figure 3 .Depend on Figure 3 It can be seen that the pore diameter is mostly distributed around 20 nm.
[0032] 4. Polarization current curve The polarization current data of the IrO2@WC / WO3 composite catalyst and the commercial IrO2 catalyst prepared in Examples 1-3 are shown in Figure 4 As can be seen from the figure, the composite catalysts obtained in Examples 1, 2, and 3 have a current density of 10 mAcm -2 When the overpotentials are 294 mV, 275 mV and 302 mV respectively, the catalytic activity is better than that of the commercial IrO2 (320 mV) catalyst at the same current density. In Examples 1-3, the catalyst prepared from the WC / WO3 carrier calcined at 1100 °C in Example 2 has the best catalytic activity.
[0033] 5. Electrochemically active area (ECSA) Figure 5 The double-layer capacitance of the IrO2@WC / WO3 composite catalyst and the commercial IrO2 catalyst obtained in Example 2 ( C dl ), among which the composite catalyst and commercial IrO2 catalyst C dl 68.6 and 37.8 mFcm respectively -2 , usually, the ECSA value of a catalyst can be obtained by C dl With oxide surface capacitance (40 μFcm -2 ) ratio, and the calculated ECSA value of the composite catalyst and commercial IrO2 is 1.715 m 2 and 0.945m 2 , indicating that the IrO2@WC / WO3 composite catalyst of Example 2 of the present invention has more electrochemical active sites and can efficiently utilize the IrO2 active sites.
[0034] 6. Electrochemical Impedance Spectroscopy Figure 6 The electrochemical impedance spectra (EIS) of the IrO2@WC / WO3 composite catalyst obtained in Examples 1-3 and the commercial IrO2 catalyst are shown in Figure 1-3, where the impedance values of Examples 1-3 and the commercial IrO2 catalyst are 10.1Ω, 5.8Ω, 15.3Ω and 27.5Ω, respectively. It can be seen that the catalyst prepared from the WC / WO3 carrier calcined at 1100°C in Example 2 can effectively accelerate the charge transfer in the OER process.
Claims
1. A method for preparing a novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology, characterized in that: The following steps are involved: (1) Sodium tungstate and sodium nitrate are added to a mixed solution of isopropanol and ethanol, and then stirred under heating conditions until completely dry, ball milled, and sintered at high temperature to obtain a WO3 nanocarrier through the action of molten salt, cooled to room temperature, centrifuged and washed, and dried to obtain the final WO3 nanocarrier; (2) The final WO3 nano-carrier obtained in step (1) is mixed with the carbon source by ball milling, transferred to a tube furnace, sintered at high temperature, cooled to room temperature, centrifuged and washed, and dried to obtain a WC / WO3 composite carrier; (3) The WC / WO3 composite support, ammonium persulfate, ammonium fluoride and iridium salt obtained in step (2) are added to a hydrothermal reactor, and a methanol solution is added, ultrasonically dispersed, heated to 180 degrees and kept warm for 4-8 hours, cooled to room temperature, centrifuged and washed, and dried to obtain an IrO2@WC / WO3 composite catalyst.
2. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: In step (1), the molar ratio of sodium tungstate to sodium nitrate is 1:(10-40), and the volume ratio of isopropanol to ethanol is 1:
1.
3. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: The stirring under heating conditions until completely dry in step (1) specifically comprises: heating to 60-80° C., stirring for 1-3 hours, and then adjusting the temperature to 100° C. and stirring until completely dry; the ball milling speed is 100 rpm / min, and the time is 30 minutes.
4. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: The high temperature sintering conditions in step (1) are: heating to 350-750°C at a heating rate of 2-5°C / min and calcining for 1-3h.
5. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: The carbon source in step (2) is urea, melamine, glucose or chitosan; wherein the high temperature sintering in step (2) is as follows: introducing a H2 mixed gas with a flow rate of 20-100 sccm and a 10% Ar / H2 ratio, heating to 1000-1200°C at a heating rate of 2°C / min, and calcining for 1-3h.
6. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 5, characterized in that: The mass ratio of the WO3 nanocarrier to the carbon source in step (2) is 1:
10.
7. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: The conditions for the centrifugal washing in steps (2) and (3) are: centrifugation at 7000-10000 rpm / min for 3-5 times.
8. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: The drying in steps (1), (2) and (3) is vacuum drying at a temperature of 50-80° C. for 5-10 hours.
9. The method for preparing the novel anode IrO2@WC / WO3 composite catalyst suitable for proton exchange membrane water electrolyzer technology according to claim 1, characterized in that: In step (3), the added mass ratio of the WC / WO3 composite carrier to the iridium content in the iridium salt is (1:0.2); the molar ratios of ammonium persulfate, ammonium fluoride and iridium in the iridium salt are (1:1:0.5) respectively; and the iridium salt is iridium trichloride, chloroiridic acid, iridium acetate, ammonium chloroiridate or potassium hexachloroiridate.
10. Use of the catalyst according to claims 1-9 in the electrolysis of oxygen in acidic water.
